NAMING THE BUILDING IN BALI ARCHITECTURE - I Ketut Adhimastra (Universitas Dwijendra, 2014)
Traditional architecture of Bali is famous in the world of global (international) because it is unique and filled with the values of local nuances associated with the religious and life stance communities based on the Bali Tri Hita Karana, namely in the field of spiritual harmony (divinity); in harmony with the surrounding natural environment (nature) and in harmony with the social environment (human). Similarly, when the masons Bali or commonly known as undagi, give the name of the building were made, they or the undagi name the buildings that made always based on some custom rules that have been accepted by the public support for the Bali building. Some of the considerations that underlie it are: (a) the position of the building in the direction of the wind; (B) the functionality or usability of the building; (C) the number of pillars or building poles; and (d) other considerations such as the chronicle (history) or a particular event.Keywords: Building, Architecture Bali